2022
DOI: 10.1002/er.8653
|View full text |Cite
|
Sign up to set email alerts
|

Design of metal phosphite decorated sponge materials for high‐performance flexible battery‐type supercapacitors

Abstract: In this work, iron and zinc phosphite [FeP and Zn 3 P 2 (ZnP)] crystals were individually decorated on a flexible, freestanding, and three-dimensional (3D) graphene sponge material (GSM) through a facile and cost-effective electrodeposition method. With the synergistic effect between metal phosphite (MP) particles and graphene, 3D FeP/GSM and ZnP/GSM electrodes displayed excellent electrochemical performances with high specific capacitances of 1872 and 908 F/g at a current density of 1 A/g and remarkable cycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…In addition, as shown in Figure 7f, the capacity retention of the asymmetric supercapacitor Ni 2 P@C/CNT//FeP/C/CNT‐2 after 10,000 cycles is 61 %, indicating that the device has good cycling stability. Compared with reported capacitors such as MnF 2 //AC, [28] NR‐NiF 2 //AC, [29] Mn 3 O 4 ‐rGO//FeP@PGNPC, [30] FeP/GEM//GSM, [31] and CoP/FeP 4 , [32] Ni 2 P@C/C/CNT//FeP/C/CNT‐2 asymmetric capacitors exhibit strong energy storage performance (Table 1), which suggests that the device has potential for certain applications.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…In addition, as shown in Figure 7f, the capacity retention of the asymmetric supercapacitor Ni 2 P@C/CNT//FeP/C/CNT‐2 after 10,000 cycles is 61 %, indicating that the device has good cycling stability. Compared with reported capacitors such as MnF 2 //AC, [28] NR‐NiF 2 //AC, [29] Mn 3 O 4 ‐rGO//FeP@PGNPC, [30] FeP/GEM//GSM, [31] and CoP/FeP 4 , [32] Ni 2 P@C/C/CNT//FeP/C/CNT‐2 asymmetric capacitors exhibit strong energy storage performance (Table 1), which suggests that the device has potential for certain applications.…”
Section: Resultsmentioning
confidence: 91%
“…The cathodic and anodic peaks on the curve are related to the charge-discharge reactions of FeP + xLi + + xe À $ Li x FeP and Li x FeP + (3À x)Li + + (3x)e À $ Li 3 P + Fe. [33] The reduction peak at 1.3 V is generated by Mn 3 O 4 -rGO//FeP@PGNPC 112 W h kg À 1 /850 W kg À 1 61 W h kg À 1 /17 kW kg À 1 5000 cycles/90 %/-A g À 1 [30] FeP/GEM//GSM 265 W h kg À 1 /2.6 kW kg À 1 56 W h kg À 1 /5.5 kW kg À 1 10000 cycles/80 %/-A g À 1 [31] CoP//FeP 4 46 W h kg À 1 /695 W kg À 1 34 W h kg À 1 /7 kW kg À 1 10000 cycles/89 %/10 A g À 1 [32] This work 71 W h kg À 1 /890 W kg À 1 38 W hkg À 1 /7.9 kW kg À 1 10000cycles/61 %/7 A g À 1 -…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that MnCo-MOF/3DG//3DG has higher energy and power density compared to other graphene-based materials, which can be attributed to its battery-type performance and electroactive and porous MOF structures. 36,37,52–57 MnCo-MOF/3DG//3DG has the energy to keep the green light emitting diode (LED) lit for 10 min (Fig. 7c) and can emit light of high intensity even after 10 min (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…11 Then, up to half of both MnCo-MOF/3DG and 3DG were immersed in this prepared polymer gel electrolyte for 1 h and dried at room temperature for 24 h after removal. 3DG materials coated on one side with PVA-KOH were sandwiched between the gel electrolyte parts, and a conductive and flexible graphene paper (GP) electrode 35,36 was placed on the outside as a current collector. Then, the ASC circuit was prepared by wrapping the outer parts with insulating tape so that the GP ends were exposed.…”
Section: Methodsmentioning
confidence: 99%